Precooling temperature relaxation technology in hydrogen refueling for fuel-cell vehicles. (28th September 2021) - Handa, Kiyoshi; Oshima, Shinji; Rembutsu, Tatsuya
Abstract: The dissemination of fuel-cell vehicles requires cost reduction of hydrogen refueling stations. The temperature of the supplied hydrogen has currently been cooled to approximately −40 °C. This has led to larger equipment and increased electric power consumption. This study achieves a relaxation of the precooling temperature to the −20 °C level while maintaining the refueling time. (1) Adoption of an MC formula that can flexibly change the refueling rate according to the precooling temperature. (2) Measurement of thermal capacity of refueling system parts and re-evaluation. Selection from multiple refueling control maps according to the dispenser design (Mathison, et al., 2015). (3) Calculation of the effective thermal capacity and reselection of the map in real time when the line is cooled from refueling of the previous vehicle (Mathison, and Handa, 2015). (4) Addition of maps in which the minimum assumed pressures are 10 and 15 MPa. The new method is named MC Multi Map. Highlights: Compatible hydrogen refueling protocol to the current existing station. Cold dispenser control and thermal mass management are merged in a simple control map selection method. A refueling with −20C precooling is possible even in summer.